Computer-Based Executive Function Training for Combat Veterans With PTSD: A Pilot Clinical Trial Assessing Feasibility and Predictors of Dropout - Clausen, Ashley N.; Thelen, Joan; Francisco, Alex J.; Bruce, Jared; Martin, Laura; McDowd, Joan; Aupperle, Robin L. (Frontiers in Psychiatry, 2019)
Background: While evidence-based PTSD treatments are often efficacious, 20-50% of individuals continue to experience significant symptoms following treatment. Further, these treatments do not directly target associated neuropsychological deficits. Here, we describe the methods and feasibility for computer-based executive function training (EFT), a potential alternative or adjunctive PTSD treatment. Methods: Male combat veterans with full or partial PTSD (n = 20) and combat-exposed controls (used for normative comparison; n = 20) completed clinical, neuropsychological and functional neuroimaging assessments. Those with PTSD were assigned to EFT (n = 13) or placebo training (word games; n = 7) at home for six weeks, followed by repeat assessment. Baseline predictors of treatment completion were explored using logistic regressions. Individual feedback and changes in clinical symptoms, neuropsychological function, and neural activation patterns are described. Results: Dropout rates for EFT and placebo training were 38.5% and 57.1%, respectively. Baseline clinical severity and brain activation (i.e., prefrontal-insula-amygdala networks) during an emotional anticipation task were predictive of treatment completion. Decreases in clinical symptoms were observed following treatment in both groups. EFT participants improved on training tasks but not on traditional neuropsychological assessments. All training completers indicated liking EFT, and indicated they would engage in EFT (alone or as adjunctive treatment) if offered. Conclusion: Results provide an initial framework to explore the feasibility of placebo-controlled, computerized, home-based executive function training (EFT) on psychological and neuropsychological function and brain activation in combat veterans with PTSD. Clinical severity and neural reactivity to emotional stimuli may indicate which veterans will complete home-based computerized interventions. While EFT may serve as a potential alternative or adjunctive PTSD treatment, further research is warranted to address compliance and determine whether EFT may benefit functioning above and beyond placebo interventions.